The Role of Surface Coordination in the Dissolution of δ-Al2O3 in Dilute Acids - Gerhard Furrer; Werner Stumm (CHIMIA)
Chemical processes at the hydrous-oxide solution interface – protonation of surface OH-groups and surface coordination with ligands (anions) – are important for understanding the dissolution of solid oxide phases. It is shown that the dissolution rate of δ-Al2O3 in dilute acids (pH 2.5-6) depends directly on the extent of surface protonation and on the concentration of surface complexes formed in the presence of oxalate, salicylate, citrate and benzoate.